International passenger perception on airport branding strategy: evidence from Malaysia - Mohd Thas Thaker, Hassanudin; Ah Mand, Abdollah; Hock Leong, Chan; Khaliq, Ahmad; Mohd Thas Thaker, Mohamed Asmy; Allah Pitchay, Anwar (2022)
This study aimed at analyzing international passenger perceptions of Kuala Lumpur International Airport (KLIA) branding strategies. We used a self- administrated questionnaire distributed to 212 international passengers at KLIA. The structured questionnaire consists of two parts: i) respondent demographic profiles, and (ii) perceptions on branding strategies. The first part collected data on gender, age and marital status, frequency of departure or arrival at KLIA, and the purpose of visiting Malaysia. The second part covered branding perception as measured by seven factors such as choice of food and beverage outlets (CFBO), selection of retail outlets (SRO), retail pricing (RP), layout and design (LD), services and entertainment (SE), service staff (SS), and logos, slogans and wordmarks (LSW) at KLIA. For this research, the Smart Partial Least Square Version 3 was used for data analysis. The findings reveal that choice of food and beverage outlets, layout and design, selection of retail outlets, retail pricing, service staff are found to be significant in the branding perception of KLIA. These findings lend support to the argument on the branding perception of the airport and offer several policy implications from a literature and practical point of view with regard to KLIA branding.